(untitled) (Journal of Hama University, 2024)
This research aimed to determine the degree to which psychological counseling students possess the soft skills necessary for the labor market at the College of Education at Tishreen University, and detecting differences in their level according to the variables (gender and work during study). In order to achieve the research objectives, the descriptive method was used, and using the questionnaire of Bajamal et al. (2023) for the soft skills needed for the labor market, that consists of (30) phrases and measures five skills: (communication, time management, problem solving, leadership and planning), and the research sample consisted of (135) male and female students in the fourth and fifth years from the Department of Psychological Counseling at the College of Education at Tishreen University,and the research reached the following results: - The degree of psychological counseling students’ possession of the soft skills necessary for the labor market was average. - The degree of possession of the skill (problem solving) was high While the degree of possession of the skills (communication, leadership, time management, and planning) was average among psychological counseling students at the College of Education at Tishreen University. - There is no difference among psychological counseling students on the questionnaire on the soft skills needed for the labor market (total score and sub-skills) according to the gender variable. - There is a difference among psychological counseling students on the questionnaire on the soft skills needed for the labor market (total score and sub-skills) depending on the variable of work during the study for the benefit of the students who work during the study.